Oil-in-water emulsion enhancement for viscious crude oil flow in pipeline - Liyana Nadirah, Mat Suli (2014)
With the increasing energy prices and the drive to reduce C02 emission, universities and industries are challenged to find new technologies in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. Traditional methods of transporting heavy crude oils in pipelines are disadvantages from both economic and environmentally perspectives. In this study, the potentials of o/w emulsion technique for transporting viscous crude oils in pipeline as alternative and cost effective method was investigated. The study began with characterisation studies of both types of crude oil and emulsion to provide understanding of fundamental issues such as conventional transportation methods, partial upgrading, pipeline heating, and dilution with lighter crude oils. The aim is to investigate the various factors affecting the preparation of stable crude o/w emulsion, the influence of the emulsion as well as to obtain optimised operating conditions, upon which further developments on pipeline transportation of viscous crudes as concentrated o/w emulsion process could be developed. Two types of crude oil samples were used in this study; heavy oil obtained from Petronas Refinery, Melaka and blend oil was formulated by 60-40% (heavy oil-light oil) which is light oil obtained from Petronas Kerteh. The Fractional Factor Design (FFD) in Design Expert 7.1.6 followed by Center Composite Desing (CCD) was used for optimization study. Results that were obtained have shown that, both crude oils used were stabilised within 1 % surfactant used. The analysis of variance (ANOVA) shown the stability was significant with R2 value at 0.9753 for heavy o/w emulsion and 0.9572 for the blend o/w emulsion. Results have indicated heavy o/w emulsion shown transitional flow while blend o/w emulsion shown turbulent flow. The addition of 40% of light oil to heavy oil has reduced the blend oil viscosity from 478.1 rnPa.s to 113.40 mPa.s. The ~heological study was successfully investigated and emulsion showed Newtonian behaviour for both types of crude oil. Meanwhile the predicted model of o/w emulsion (using Power Law) showed at 30-60% by volume shown non-Newtonian shear thinning flow behaviour. The results obtained was exposed the capability of o/w emulsion technique as another promising pipeline technique in the transport of viscous crude as concentrated o/w emulsions. Further works are nevertheless required to provide deeper understanding of the mechanism involved to facilitate development of an optimum system applicable to industry.